Clostridium subterminale Septicemia in a Patient with Metastatic Gastrointestinal Adenocarcinoma - Kevin M. Trapani; Leigh J. Boghossian; Elizabeth Caskey (Case Reports in Infectious Diseases)
Clostridium subterminale is a rare member of the Clostridiaceae family that is rarely cultured. This report examines a case of Clostridium subterminale cultured from the blood of a 72-year-old man who was ultimately diagnosed with metastatic gastrointestinal (GI) adenocarcinoma. The patient was receiving treatment for nosocomial pneumonia prior to culture of the C. subterminale, which led to suspicion for malignancy. Extensive GI and oncologic workup demonstrated multiple comorbidities and a primary GI cancer, which likely caused a breach in the GI mucosa and C. subterminale entrance into the bloodstream. After a prolonged intensive care unit (ICU) stay, the patient died on hospital day 23. Though rarely reported, C. subterminale septicemia has been demonstrated in patients with malignancy, specifically of the GI tract. Therefore, this case represents a typical C. subterminale septicemia patient. Given the prevalence of Clostridia and the contemporary emergence of multidrug resistant (MDR) microorganisms, both typical and atypical cases regarding rare members of the species have a significant role in the clinical management and public health planning.